Análise da resposta acústica em sedimentos marinhos - Menandro, Pedro Smith (2014)
Submarine geoacoustics helps in understanding the behavior of propagation and attenuation of sound in sediment, providing an information set which assists the major data interpretation approaches. The detection of muddy deposit through high resolution acoustic records is generally easy, usually appearing as free reflection layers. However, this acoustic response depends on the frequency used and other characteristics of the deposit, even of the water column. The dynamics of these muddy layers may have influence in many areas, from engineering and harbor maintenance, to biology and studies of impact on benthic biota. The development of a rapid and efficient mapping method for these deposits seems to be a demand for knowledge advance of the processes involved in the transport, deposition and suspension. Thus, this study has two main approaches divided into two independent studies: i) investigate how the acoustic signal response from different sources changes with the frequency and sediment physical properties (grain size and density), and ii) associate variations observed in the acoustic records with sediment mobility over a tidal cycle. The dataset consists of high-frequency geophysical records ( 3.5, 33 and 210 kHz ) , sediment physical properties, in situ density , hydrodynamics and distribution of suspended particulate matter, which were collected at the North Channel of Amazon River . The first chapter showed that different survey methods at the same area can provide different results. Furthermore, the frequency and density were important properties to understand the relationship between surface sediment and acoustic features. The second chapter was an attempt to evaluate sediment dynamics through acoustic system, and showed that the changes in the processes of sediment transport were recognized by the ADCP and OBS allowing to distinguish the acoustic echo sounder records and to interpret sedimentary dynamic processes.